Star−Disk Collisions: Implications for Quasi-periodic Eruptions and Other Transients near Supermassive Black Holes - Philippe Z. Yao; Eliot Quataert; Yan-Fei Jiang; Wenbin Lu; Christopher J. White (The Astrophysical Journal)
We use Athena++ to study the hydrodynamics of repeated star−accretion disk collisions close to supermassive black holes, and we discuss their implications for the origin of quasi-periodic eruptions (QPEs) and other repeating nuclear transients. We quantify the impact of the collisions on the stellar structure, the amount of stripped stellar debris, and the orbital properties of the debris. We provide simple fitting functions for the stellar mass loss per collision; the mass loss is much larger after repeated collisions, due to the dilute stellar atmosphere shock-heated in earlier collisions. The lifetime of the QPE-emitting phase set by stellar mass loss in star−disk collision models for QPEs is thus at most ∼1000 yr; it is shortest for eRO-QPE2, of order a few decades. The mass of the stripped stellar debris per collision and its orbital properties imply that currently observed QPEs are not powered by direct star−disk collisions but rather by collisions between the stellar debris liberated in previous collisions and the accretion disk (“circularization shocks”). We discuss how the hydrodynamics of this interaction can explain the diverse timing properties of QPEs, including the regular timing of GSN 069 and eRO-QPE2 and the large flare-to-flare timing variations observed in eRO-QPE1. QPEs with recurrence times of many days, if observed, may have more regular timing.